Power and Age - Sam Maghimbi (Nordic Journal of African Studies)
Spencer (1965, 1988, 1993, 2003) theorizes two distinct strands in the life course of a Maasai male. The first strand is the building of a cattle herd and a family, and the second is developing involvement in the age class system. The second strand is overemphasized in Spencer’s analysis of Maasai society. The age class system attracts nearly euphoric attention from Spencer and other authors on the Maasai. This stance has led to a point where the materiality of Maasai life (cattle) is discussed but is hidden behind a discussion of the age system. This article argues that more weight should be given to the first strand of Maasai life mentioned by Spencer. Maasai society may still be largely organized along gerontocratic lines, but nevertheless the power of Maasai men is derived from the cattle herd and from their control of their families.